Spatial patterns in a photobiochemical system - Aon, Miguel (1989)
Illumination of a system consisting of a vertical tube containing an unstirred homogeneous suspension of thylakoids in an imposed linear concentration gradient of an electron acceptor, 2,6-dichloroindophenol, gave rise to a one-dimensional banded pattern of the acceptor that evolved in a time-dependent manner. The spatial pattern was obtained only within certain parameters of the dichloroindophenol gradient and with certain concentrations of thylakoids. Various numbers of bands were obtained by varying the gradient parameters, the thylakoid concentration, or both. Pattern formation was reaction-dependent since inhibition of the water-splitting system, either by a physical (heating) or by a chemical (methylamine) method, resulted in abolition of the spatial periodicity. Obtaining the self-organized redox transition of dichloroindophenol in a gelled medium suggests that pattern formation in this system could be explained mainly by a reaction-diffusion mechanism.